Meta-Analysis of Potent P2Y12-ADP Receptor Antagonist Therapy Compared to Clopidogrel Therapy in Acute Coronary Syndrome Patients with Chronic Kidney Disease - Bonello, Laurent; Laine, Marc; Lemesle, Gilles; Puymirat, Etienne; Dabry, Thibaut; Thuny, Franck; Paganelli, Franck; Aradi, Daniel; Frere, Corinne; Burtey, Stéphane; Sibbing, Dirk; Mancini, Julien (Thrombosis and Haemostasis, 2018)
Background The clinical benefit of anti-platelet agents in patients with chronic kidney disease (CKD) is uncertain. In addition, the risk–benefit ratio of potent oral P2Y12-adenosine diphosphate (ADP) receptor antagonists (PPAs), namely, prasugrel and ticagrelor, compared with clopidogrel in CKD patients suffering from acute coronary syndrome (ACS) remains unknown.Objective We performed a meta-analysis of all studies comparing the clinical outcomes of PPA and clopidogrel therapy in CKD patients suffering from ACS.Methods We searched PubMed, the Cochrane library, Google Scholar, Clinical trial.org and the abstracts of international cardiology congresses from April 2000 to October 2017. Clinical studies comparing PPA with clopidogrel in ACS patients with CKD were selected. Our literature research identified five studies which were included in the meta-analysis. The primary endpoint was a composite of major adverse cardiovascular events (MACEs) at the latest follow-up available. Secondary endpoint included bleedings.Results We included data from three sub-group analysis of randomized clinical trials and two prospective observational studies (n = 31,234). Overall, PPAs were associated with lower rates of major cardiovascular events, with a pooled hazard ratio (pHR) of 0.88 (95% confidence interval [CI]: 0.79–0.99; p = 0.03), without increased bleedings (pHR = 1.10) (95% CI: 0.95–1.27; p = 0.18). In a sensitivity analysis restricted to studies enrolling invasively managed patients, the benefit of PPA on MACE was maintained (pHR = 0.85) (95% CI: 0.77–0.93; p < 0.001), including a reduction in mortality (pHR = 0.82) (95% CI: 0.7–0.96; p = 0.016).Conclusion Compared with clopidogrel, PPAs were associated with a reduced rate of MACE without increased bleedings in CKD patients with ACS. Among invasively managed patients, this benefit from PPA included a reduction in mortality.
Keywords: acute coronary syndrome; anti-platelet; chronic kidney failure; outcome; percutaneous coronary intervention